Clinical application of endoscopic surgery using a gasless unilateral transaxillary approach in the treatment of primary hyperparathyroidism - Zhang, Wan-Chen; Lu, Dong-Ning; Xu, Jia-Jie; Guo, Hai-Wei; Ge, Ming-Hua; Zheng, Chuan-Ming (Frontiers in Surgery, 2022)
Objectives: To investigate the safety and feasibility of gasless axillary parathyroid surgery in the treatment of primary hyperparathyroidism. Methods: A total of 12 patients who received gasless axillary parathyroidectomy (endoscope group) and 14 patients who received traditional open parathyroidectomy (open group) from January 2019 to April 2022 were screened and included. The differences in baseline characteristics, surgical efficiency, incidence rate of complications, changes in biochemical indicators and incision satisfaction between the two groups were analyzed and compared. Results: The proportion of young patients was higher in the endoscopic group than in the open group, and the difference was statistically significant [(41.33 ± 13.65) years vs. (58.00 ± 9.44) years, P < 0.01]. The differences in the operation time, intraoperative blood loss, postoperative drainage volume, hospital stay and surgical efficiency between the two groups yielded no statistical significance (P > 0.05). Patients in the open group had more significant neck pain 3 days after surgery (P = 0.046), but the degree of pain 3 months after surgery was the same in the 2 groups (P = 0.432). Evaluation of postoperative mature stage scar and incision satisfaction regarding aesthetics in the endoscope group were significantly superior to that in the open group [ (1.92 ± 0.92) points vs. (0.92 ± 1.00) points, P = 0.017 and (1.57 ± 0.51) points vs. (1.00 ± 0.013) points, P = 0.013, respectively]. No statistical significance was found in terms of incidence rate of postoperative fever (P > 0.05). No temporary recurrent laryngeal nerve injury, postoperative bleeding, incision hematoma infection and other complications were observed. Comparing the two groups, extent in the levels decrease of PTH was similar to that of serum calcium and phosphorus (P < 0.05), where most patients experienced transient hypocalcemia after operation yielding no significant difference in incidence (P = 0.225). During a follow-up period of 3 to 36 months, a total of 1 patient in the open group experienced recurrence at 10 months after surgery and was treated non-surgically. Conclusion: Gasless axillary approach to parathyroid surgery for primary hyperparathyroidism possesses good safety and patient satisfaction in terms of aesthetics.